On the overall response of elastomeric solids with pressurized cavities - Idiart, Martín Ignacio (2012)
This work provides a means of accounting for the presence of pressurized cavities on the overall response of elastomeric solids undergoing large deformations. The main idea is to refer the kinematics to a stress-free configuration and to express the overall response of the elastomer with pressurized cavities in terms of its overall response when the cavities are vacuous. This is achieved via a change of variables valid whenever the common assumption of incompressibility is used for the elastomeric matrix. The result permits then to incorporate straightforwardly the effect of internal pressure on any micromechanical model already available for elastomeric solids with vacuous cavities. The resulting models account for constitutive and geometric nonlinearities as well as for deformation-dependent internal pressure concomitant with large deformations. Sample results for isotropic porous rubbers under plane-strain conditions are provided and discussed.